2014
DOI: 10.1158/1055-9965.epi-14-0423
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Diseases and Risk of Hematopoietic Malignancies in a Cohort of Postmenopausal Women: A Report from the Iowa Women's Health Study

Abstract: Background Allergic diseases signify immune dysregulation attributable to underlying genetics and environmental exposures. Associations between various allergies and hematopoietic cancers have been observed, albeit inconsistently, however few prospective studies have examined the risk, and even fewer among older adults. Methods We examined risk of incident hematopoietic cancers in those reporting allergic diseases in a population-based cohort of 22,601 older women (Iowa Women’s Health Study). Self-reported a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 63 publications
2
18
0
1
Order By: Relevance
“…These findings are in line with the study by Linabery et al (2014). They reported no association between allergic diseases other than asthma and haematological malignancies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in line with the study by Linabery et al (2014). They reported no association between allergic diseases other than asthma and haematological malignancies.…”
Section: Discussionsupporting
confidence: 93%
“…Outcomes were MDS and other incident haematological malignancies identified in the State Health Registry of Iowa (Linabery et al , 2014). Although the underlying mechanism is unknown, immune dysregulation in MDS is evident, as some subtypes respond to the treatment with immunosuppressive or immunomodulatory agents (Saunthararajah et al , 2003; List et al , 2005; Mollgard et al , 2011; Duong et al , 2012).…”
mentioning
confidence: 99%
“…In the Vitamins and Lifestyle (VITAL) cohort (17), self-reported plant, tree, or pollen allergies at baseline were associated with increased future risk of mature B-cell neoplasms (excluding CLL/SLL and MM). Consistent with our findings, a recent report from the Iowa Women’s Health Study found that self-reported allergic diseases were associated with a reduced risk of lymphoid neoplasms among those living in rural areas; no association was observed among residents in urban areas (18). …”
Section: Discussionsupporting
confidence: 92%
“…Findings from cohort studies in the general population have been inconsistent, although the definitions of allergies and NHL/subtypes varied between studies (13, 1518). In a nested case-control study within the Finnish Maternity Cohort (13), risk of NHL was reduced in relation to specific IgE seropositivity in samples collected shortly prior to NHL diagnosis but not in samples collected ≥10 years before diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation